A Comparative Analysis of Gremlin-1 (GREM1), Hyaluronic Acid Synthetase-2 (HAS2), and Prostaglandin-Endoperoxide Synthase-2 (PTGS2) Expression in Cumulus Cells Among Women with Diminished Ovarian Reserve Following Rescue In Vitro Maturation (r-IVM) - Mohd Faizal Ahmad; Marjanu Hikmah Elias; Norazilah Mat Jin; Muhammad Azrai Abu; Saiful Effendi Syafruddin; Ani Amelia Zainuddin; Shah Shamsul Azhar; Nao Suzuki; Abdul Kadir Abdul Karim (MDPI AG, 2026)
Indexed by WOS / SCOPUS / ERA